The maternal origin of indigenous domestic chicken from the Middle East, the north and the horn of Africa - Al-Jumaili, A.S.; Boudali, S.F.; Kebede, A.; Al-Bayatti, S.A.; Essa, A.A.; Ahbara, A.; Aljumaah, R.S.; Alatiyat, R.M.; Mwacharo, Joram M.; Bjørnstad, G.; Naqvi, A.N.; Gaouar, S.B.S.; et al. (Springer, 2020)
Indigenous domestic chicken represents a major source of protein for agricultural communities around the world. In the Middle East and Africa, they are adapted to hot dry and semi-dry areas, in contrast to their wild ancestor, the Red junglefowl, which lives in humid and sub-humid tropical areas. Indigenous populations are declining following increased demand for poultry meat and eggs, favouring the more productive exotic commercial breeds. In this paper, using theD-loop of mitochondrial DNA as a maternally inherited genetic marker, we address the question of the origin and dispersal routes of domestic chicken of the Middle East (Iraq and Saudi Arabia), the northern part of the African continent (Algeria and Libya) and the Horn of Africa (Ethiopia).The analysis of the mtDNAD-loop of 706 chicken samples from Iraq (n = 107), Saudi Arabia (n = 185), Algeria (n = 88), Libya (n = 23), Ethiopia (n = 211) and Pakistan (n = 92) show the presence of five haplogroups (A, B, C, D and E), suggesting more than one maternal origin for the studied populations. Haplogroup E, which occurred in 625 samples, was the most frequent in all countries. This haplogroup most likely originates from the Indian subcontinent and probably migrated following a terrestrial route to these different countries. Haplotypes belonging to haplogroup D were present in all countries except Algeria and Libya, it is likely a legacy of the Indian Ocean maritime trading network. Haplogroup A was present in all countries and may be of commercial origin. Haplogroup B was found only in Ethiopia. Haplogroup C was only detected in the South-Western region of Saudi Arabia and in Ethiopia.The results support a major influence of the Indian subcontinent on the maternal diversity of the today’s chicken populations examined here. Most of the diversity occurs within rather than between populations. This lack of phylogeographic signal agrees with both ancient and more recent trading networks having shaped the modern-day diversity of indigenous chicken across populations and countries.